Pembinaan Usaha Rumahan Keripik Pangsit Melalui Bantuan Modal Dan Pemberdayaan Berbasis Digital - Srie Wijaya Kesuma Dewi; Yunika Komalasari; R. Dewi Sulastriningsih; Ricky Firmansyah; Phitsa Mauliana; Nanang Hunaifi (Jurnal Masyarakat Mengabdi Nusantara, 2023)
Community poverty alleviation must be addressed more innovatively, creatively and skillfully in order to be able to create new business opportunities (for example through entrepreneurship) to meet their various needs. Entrepreneurship is one way to overcome poverty and reduce unemployment rates. Among several examples of this entrepreneurship is the home industry, namely a home industry where the business is done at home which empowers the people around the environment and reduces unemployment by absorbing it. In connection with this condition, there are several problems in terms of economic empowerment through the home industry in the food sector, including the low level of knowledge and understanding of home industry players, especially in relation to marketing, including online promotion, and the low level of human resource capacity of home business actors. The method used in this community service activity is digital-based empowerment in the form of online marketing and product promotion techniques. Community service activities with partners in the wonton chips home business that have been carried out have resulted in the fact that digital-based empowerment is very necessary. Considering the times and technological advances, it is a necessity that business actors are able to adapt to these conditions. Through this activity, partners gain an understanding of digital-based empowerment, product diversification, and the important role of home business actors in supporting the nation's economy. This digital-based empowerment is expected to increase production, marketing and business turnover, as well as to build relationships between universities and the community.